Jom ha-Šo'a...počátky jednoho svátku - Zbyněk Tarant (AntropoWebzin, 2011)
If one looks at the calendar, one will find there 'International Holocaust Rememberance Day' on 27th of January. This day was set by the UN General Assembly in 2005 and it refers to the anniversary of Auschwitz liberation. However, if one looks at the Israeli calendar, or any of the Jewish Luakh haShannah's, one will find there another day of mourning that is actually far older. The Yom HaShoah was set according to the Hebrew calendar and refers not to the liberation of Auschwitz, but to the Warsaw ghetto uprising. Today, this day of mourning is an interesting relict of the pioneer, upbuilding era that preferred the stories of heroes to those of victims. This article attempts to map the very beginning of the Yom HaShoah commemoration, by using Hebrew sources that were never published before in the Czech language. The story of Yom HaShoah in the context of the young state of Israel in the 1950s is an interesting case-study on the issue of how the contemporary political and public discourse affects the collective memory of  future generations.